2018
DOI: 10.3390/ijms19103087
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NADPH Oxidase Activation by Apocynin Rescues Seizure-Induced Reduction of Adult Hippocampal Neurogenesis

Abstract: Apocynin, also known as acetovanillone, is a natural organic compound structurally related to vanillin. Apocynin is known to be an inhibitor of NADPH (Nicotinamide adenine dinucleotide phosphate) oxidase activity and is highly effective in suppressing the production of superoxide. The neuroprotective effects of apocynin have been investigated in numerous brain injury settings, such as stroke, traumatic brain injury (TBI), and epilepsy. Our lab has demonstrated that TBI or seizure-induced oxidative injury and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Some studies have demonstrated the neuroprotective effects of NOX2 inhibition or modulation, which reduces neuroinflammation and improves behavioral function in chemoconvulsant-induced epilepsy models. [32][33][34] Recently, we demonstrated the role of nitro-oxidative stress in both kainite-and diisopropylfluorophosphate (DFP)-induced epileptogenesis and cognitive and motor dysfunction. 14,35 These studies strongly support the role of oxidative stress in brain pathogenesis and the therapeutic potential of NOX2 inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated the neuroprotective effects of NOX2 inhibition or modulation, which reduces neuroinflammation and improves behavioral function in chemoconvulsant-induced epilepsy models. [32][33][34] Recently, we demonstrated the role of nitro-oxidative stress in both kainite-and diisopropylfluorophosphate (DFP)-induced epileptogenesis and cognitive and motor dysfunction. 14,35 These studies strongly support the role of oxidative stress in brain pathogenesis and the therapeutic potential of NOX2 inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…The brain is susceptible to oxidative stress because of the high lipid content and oxidative metabolism (Azam et al, 2012). This was proven in experimental animals which showed oxidative damage after pilocarpine-induced seizure model (Lee et al, 2018). Data from previous studies reported that recurrent seizures increase the reactive oxygen species (ROS) in the brain (Frantseva et al, 2000;Freitas et al, 2005;Barros et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Apocynin has emerged as a promising inhibitor of Nox2 NADPH oxidase used for animal models of human oxidative-stress related diseases. 8,9,11,26 However, there were discrepancies in the literature regarding the way that apocynin reduces ROS production in cells and in tissues, and no study had investigated its PKPD profiles in major tissues. The current study by investigating apocynin PKPD in mice demonstrated, for the first time, that apocynin after iv injection was distributed quickly into major organs, that is, heart, liver, and the brain and inhibited ROS production in these organs.…”
Section: Discussionmentioning
confidence: 99%
“…6 Apocynin had been widely used as a Nox2 inhibitor in animal models of oxidative stress-related cardiovascular, metabolic, liver and neurodegenerative diseases. [8][9][10][11] However, there are discrepancies in the literature regarding the action of apocynin to reduce oxidative stress. For example, several studies had reported that diapocynin was a metabolite of apocynin, that apocynin acted through diapocynin.…”
Section: Introductionmentioning
confidence: 99%